ANALISIS PENGARUH SUHU PEMANASAN, WAKTU PEMANASAN DAN SUHU PEMBUKAAN TERHADAP CACAT WARPAGE DAN FLASHING PADA MESIN HOT PRESS PLASTIK HDPE - Sitanggang, Rafael; Indra Partha, Cokorde Gede; Arta Wijaya, I wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p7, 2024)
The current issue of plastic waste has not yet received appropriate handling, resulting in the inadequate control of plastic waste management practices. Particularly, High Density Polyethylene (HDPE) is still widely encountered. HDPE is a thermoplastic made from petroleum with a melting temperature of 160ºC-240ºC, characterized by being slightly cloudy, transparent, and elastic. This research will conduct testing using a complete randomized design (RAL) factorial analysis with 3 factors to determine the influence of factor A (heating temperature), the influence of factor B (heating time), and the influence of factor C (opening temperature) on flashing defects and warpage defects in HDPE plastic. Based on the testing of flashing defects, the significant influencing factors are factor A (heating temperature), factor B (heating time), factor C (opening temperature), and the interaction of factors AB (heating temperature and heating time). Meanwhile, the significant influencing factors on warpage defects are factor A (heating temperature), factor B (heating time), and the interaction of AB (heating temperature and heating time). Based on this research, the characteristics of HDPE plastic can be determined.